2021
DOI: 10.1016/j.ebiom.2021.103504
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun mass spectrometry-based lipid profiling identifies and distinguishes between chronic inflammatory diseases

Abstract: Background Localized stress and cell death in chronic inflammatory diseases may release tissue-specific lipids into the circulation causing the blood plasma lipidome to reflect the type of inflammation. However, deep lipid profiles of major chronic inflammatory diseases have not been compared. Methods Plasma lipidomes of patients suffering from two etiologically distinct chronic inflammatory diseases, atherosclerosis-related vascular disease, including cardiovascular (C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 66 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…The risk factors are ordered based on the model itself, which provided more directions and basis for us to improve the SLE classification criteria. On the other hand, there are 3 studies [ 20 , 22 , 23 ] that performed analyses for blood polypeptides and lipids, and 1 study [ 21 ] distinguished SLE patients from normal people through skin imaging examination. All of these studies yielded decent results and provided more directions for early identification of SLE in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk factors are ordered based on the model itself, which provided more directions and basis for us to improve the SLE classification criteria. On the other hand, there are 3 studies [ 20 , 22 , 23 ] that performed analyses for blood polypeptides and lipids, and 1 study [ 21 ] distinguished SLE patients from normal people through skin imaging examination. All of these studies yielded decent results and provided more directions for early identification of SLE in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven hundred and sixty-six (1166) ineligible articles were excluded after browsing the abstracts and titles, and full texts of the remaining sixty (60) articles were read. Finally, a total of eighteen (18) studies were included, in which ten (10) [15][16][17][18][19][20][21][22][23][24] focused on SLE and the remaining eight (8) [25][26][27][28][29][30][31][32] on NPSLE. Te study selection process is shown in Figure 1, and the characteristics of included studies are shown in Tables 1 (for SLE) and 2 (for NPSLE).…”
Section: Study Selection and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Regarding the ChA concentrations employed, one should bear in mind that liposomes are not very efficient vehicles for ChA delivery (less than 3% of ChA is internalized) , and so we expect the "real" ChA concentrations to be on the micromolar range. This corresponds to the range of concentrations found in the plasma of CVD patients (Domingues et al, 2021;Matthiesen et al, 2021).…”
Section: Discussionmentioning
confidence: 56%
“…In contrast with the vast amount of literature on lysosome dysfunction in macrophages, very little is known about lysosome dysfunction in VSMCs. Here we found that ChA, a stable end oxidation product of cholesteryl linoleate and arachidonate found increased in plasma of CVD patients (Domingues et al, 2021;Matthiesen et al, 2021) accumulates in VSMCs and causes lysosome malfunction, recapitulating many of the effects seen with oxLDL, including induction of foam cell formation. We also demonstrate that, as consequence of these alterations, these cells become stiffer, migrating and proliferating less.…”
Section: Discussionmentioning
confidence: 85%
“…They would also partition via passive diffusion and trans-membrane translocation into all membranes and the cytosol of neighboring cells. Considering that cholesteryl linoleate, the predicted precursor of ChA, is the most abundant cholesteryl ester in plasma (Matthiesen, Lauber et al 2021),…”
Section: Discussionmentioning
confidence: 99%